The sweetness of forgetting - Harmel, Kristin (Gallery Books, 2012)
In this heartwarming story of love, family and baked goods, bakery owner Hope McKenna-Smith, the divorced mother of a surly preteen girl, is summoned by her aging grandmother who, ready to reveal the secret she has kept for 70 years, sends her on a journey across the world that will forever change her life.